Prognostic value of the neutrophil/lymphocyte ratio in enteropancreatic neuroendocrine tumors. Issue 3 (March 2020) - Grenader, Tal; Pavel, Marianne E.; Ruszniewski, Philippe B.; Ćwikła, Jarosław B.; Phan, Alexandria T.; Raderer, Markus; Sedláčková, Eva; Cadiot, Guillaume; Wolin, Edward M.; Capdevila, Jaume; Wall, Lucy; Rindi, Guido; et al.
Abstract : Accessible prognostic tools are needed to individualize treatment of neuroendocrine tumors (NETs). Data suggest neutrophil/lymphocyte ratios (NLRs) have prognostic value in some solid tumors, including NETs. In the randomized double-blind CLARINET study (NCT00353496; EudraCT 2005-004904-35), the somatostatin analog lanreotide autogel/depot increased progression-free survival (PFS) compared with placebo in patients with inoperable or metastatic intestinal and pancreatic NETs (grades 1–2, Ki-67 < 10%). The exploratory post-hoc analyses presented here evaluated the prognostic value of NLR in the CLARINET study cohort, in the context of and independently from treatment. Kaplan–Meier PFS plots were generated for patients with available NLR data, in subgroups based on NLR values, and 24-month survival rates were calculated. P values and hazard ratios for prognostic effects were generated using Cox models. 31216222 Baseline characteristics were balanced between lanreotide autogel/depot 120 mg ( n = 100) and placebo ( n = 101) arms. Irrespective of treatment, raw 24-month PFS rates were comparable across subgroups based on NLR tertiles [37.3% (low), 38.8% (middle), 38.8% (high); n = 67 per group] and NLR cutoff of 4 [38.1% (NLR ⩽ 4; n = 176), 40.0% (NLR > 4; n = 25)]. Furthermore, NLRs were not prognostic in Cox models, irrespective of subgroups used. The therapeutic effect of lanreotide autogel/depot 120 mg was independent of NLRs ( P > 0.1). These exploratory post-hoc analyses in patients with advanced intestinal and pancreatic NETs contrast with previous data suggesting NLR has prognostic potential in NETs. This may reflect the inclusion of patients with lower-grade tumors or use of higher NLR cutoff values in the current analysis.